PERAN AYAH DALAM PENANGANAN STUNTING - Triyani, Irma; Mather, Mather; Desvicasari, Tika (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Background: Stunting is a chronic nutritional problem that remains a major public health challenge in Indonesia. This condition results from prolonged nutritional deficiencies, particularly during the first 1,000 days of life, and affects children’s physical growth, cognitive development, and future productivity. One of the key factors in preventing stunting is the father’s role in childcare and fulfilling the child’s nutritional needs. Objective: To determine the relationship between the father’s role and the incidence of stunting in the working area of Sungai Ambawang Public Health Center, Kubu Raya District. Methods: This study used a quantitative approach with a cross-sectional design. A total of 90 respondents were selected using the simple random sampling technique. Data were collected through a structured questionnaire and analyzed using the Chi-Square test. Results: A total of 38.9% of children were stunted, and there was a significant relationship between the father’s role and the incidence of stunting (p = 0.000). Conclusion: The better the father’s role in childcare, nutrition fulfillment, and health-related decision-making, the lower the risk of stunting in children.